RANCANGAN SISTEM ABSENSI SISWA OTOMATIS BERBASIS SMART QR CARD MENGGUNAKAN ALGORITMA BCRYPT - Renaldi, Encik Yoega; Sitohang, Sunarsan (Computer Science and Industrial Engineering, 2023)
Various problems due to shortages in attendance are still implementing the system manual method so that the teacher feels that it has reduced flexibility in attendance. Following up on the problem, system changes must occur in order to support the attendance program. The system that was built applies some of the technology (internet of things) with a combination of hardware that functions to scan student cards of the Smart Quik Response Card type and web-based software for processing machine data with a MySQL database. The method of choice for software design is to apply bcrypt as password security at login to overcome breaches in attendance data. The results of this study built an automatic attendance system based on a smart quik response card. Based on testing by applying the blackbox method to accurately assess the attendance system that has been built, it gets a compatible score or runs smoothly for each trial feature. After experimenting with the implementation at the research location, it can be concluded that the process of absenteeism that occurs at school aims to make teachers more efficient and facilitate administration in using the application system to become disciplined and timely students.